Nonoperative treatment of liver injury caused by firearm: a case report - Fiamoncini, Heloiza; Adriani Frainer , Djulia; da Silveira Welter, Carolina; Theis Galdino, Claudia (Seven Editora, 2023)
Nonoperative tratment (NOT) of blunt liver injury is a widespread practice that has a high sucess rate (82- 100%). Because of this, NOT has been used in cases of penetrating liver injury. However, despite the positive outcomes, the indication of NOT in these cases is controversial. Due to high incidence of associated thoracoabdominal injuries, this treatment modality requires a careful selection of the patient. This report presents a case of a victim of a firearm injury whose projectile was lodged in segment II of the liver, and this injury was managed with NOT, without any liver complications. However, due to its thoracic path to the abdominal cavity, it was necessary to approach the pleural empyema condition, with good evolution, without other associated complications. DOI: 10.56238/pacfdnsv1-015